0795 CO2 Measurements inInfants and Young Children Diagnosed with Central Sleep Apnea by Polysomnography. (27th April 2018) - Dosier, L B; Roth, H; Fan, Z; Vaughn, B V
Abstract: Introduction: Optimal treatment strategies for central sleep apnea (CSA) in children are debated. Better understanding of clinical characteristics of young children diagnosed with CSA may be able to guide and predict response to current therapies. Methods: Retrospective chart review was performed at a medium-sized children's hospital sleep center, of children 44 weeks gestational age to 3 years with a central apnea index (CAI) greater than or equal to 2.0 on polysomnography. Clinical characteristics including associated medical conditions, oxygen levels, and carbon dioxide levels were reviewed. Results were compared using standard descriptive statistics. Results: Of the 226 sleep studies performed on children between 44 weeks gestational age and 3 years of age, from October 2015 to September 2017, 25% (56/226) had a CAI greater than or equal to 2. Average age of the children with CAI greater than or equal to 2 is 1.67 years and average CAI 6.63 events per hour. CO2 monitoring was performed using end tidal CO2 for 61%, transcutaneous CO2 for 26%, and was technically limited in 13% of the studies. Of the children with CSA, 29/56 (52%) had low to normal average CO2 while asleep (CO2 less than 45torr), 14/56 (25%) had elevated average sleep CO2 (CO2 greater than or equal to 45torr), and 13/56 (23%) had technically limited studies. Evaluation of CO2 using maximal CO2 revealed 28/56 (50%) had low to normal maximal sleep CO2 (CO2 less than 50torr), 16/56 (29%) had elevated maximal sleep CO2 (CO2 less than or equal to 50torr), and 12/56 (21%) had technically limited studies. When comparing average CO2 to maximal CO2 29% of the children changed classification with respect to whether they had normal or elevated CO2 status. Conclusion: There are multiple measurements used to evaluate CO2 in sleep, and CO2 levels are not always reliable. These results indicate that in some cases there are discrepancies between CO2 measures in patients with CSA, underscoring the importance of further investigation into the use of CO2 parameters obtained during polysomnography to guide therapy. Support (If Any): None.